Respostas fisiológicas e citogenéticas em raízes de Allium cepa L. expostas às amostras de àgua e sedimento de três barragens ao longo da bacia do Rio Santa Maria da Vitória (ES, Brasil) - Coelho, Edvar Junior Roncetti. (2017)
The environmental impacts caused to the water bodies are directly related to the human population increase and therefore their anthropic activities. Bioassays with higher plants are very common to determine the environmental quality of a polluted ecosystem. Thus, this study aim to evaluate the quality of water and sediment samples from Duas Bocas, Rio Bonito and Suíça dam in the Santa Maria da Vitória river basin, using physicochemical parameters, toxicological and biochemical tests in Allium cepa L. Two campaigns were carried out (March and November 2016) and one sampling station was defined at the Duas Bocas dam (DB), three at the Rio Bonito dam (RB1, RB2 and RB3) and two at the Suíça dam (SU1 and SU2). Limnological parameters and trace element quantification were analyzed. From the sediment samples the solubilized was extracted for the accomplishment of tests. The bioassays with A. cepa were carried out by means of germinated seeds in exposure to water and sediment samples from each sampling station and negative (distilled water) and positive (MMS 4x10-4 mM) controls. The evaluation of toxicity parameters were obtained through analisys of germination and root growth and the cytogenetics evaluation involved the analysis of mitotic index, chromosomal aberration index, mutagenicity index in meristematic roots and frequency of micronuclei in F1 of A. cepa. For biochemical analysis of oxidative stress, SOD, CAT, GST, GSH and LPO were quantified. In the statistical analysis, Shapiro-Wilk was used followed by ANOVA and Scott Knott (p <0.05) and PCA to relate trace element data to biochemical data. Trace elements above the legislation were quantified in Duas Bocas (Zn), Rio Bonito (Fe, Zn and As), and Suíça (Zn, Ni and Fe), mainly in samples from the first campaigns. Rio Bonito and Suíça dams revealed a possible cytotoxic, mutagenic and genotoxic potential in the campaigns for both water and sediment samples. Duas Bocas dam presented cytotoxic and genotoxic potential. The cytogenetic damages were higher in the sediment samples, especially in SU2 during the first campaign, suggesting relation with the concentrations of Ni and Zn in this sampling station. In the biochemical analysis, the samples of the first campaign shows higher activity, and according to PCA, the activity of these enzymes were possibly related to the concentrations of certain metals in the samples. The relation between cytogenetic data and biochemical biomarkers was close, especially in water samples, and we can affirm that A. cepa is an excellent organism test to verify environmental quality, complementing the physical and chemical analyzes performed in biomonitoring polluted environments.